Classifying the orbits of the generalized symmetric spaces for SL2(Fq). Issue 4 (2nd April 2020) - Buell, C.; Helminck, A.; Klima, V.; Schaefer, J.; Wright, C.; Ziliak, E.
Abstract: In this paper we will discuss the orbits of the fixed-point group on the tori of the generalized symmetric spaces of SL 2 ( k ) where k is a finite field. Specifically, we will provide a characterization and classification of the maximal k -split and k -anisotropic tori.